Vaccines Immunize People; Legislation Immunizes Vaccine Manufacturers. Legislation in the United States Regulating Liability for the Manufacture, Distribution and Administration of Vaccines - Heller, Thomas Allan (Collected Papers of Thomas A. Heller, 2025)
Infectious diseases have caused widespread misery, and have wreaked havoc physically, mentally, economically, politically, and socially. Fortunately, in more recent years, scientists have developed vaccines. Vaccines are generally very safe, but cause side effects in a small percentage of cases. The United States Congress has passed two major pieces of legislation that provide sweeping tort immunity to vaccine manufacturers and others. In 1986 Congress passed the National Childhood Vaccine Injury Act (NCVIA) and in 2005 it passed the Public Readiness and Emergency Preparedness Act (PREP ACT). Both Acts were passed to encourage manufacturers to develop vaccines, particularly in times of public emergencies, in exchange for expansive liability protection. Both Acts established no-fault type compensation schemes to compensate those suffering injury or death from vaccines without having to resort to typical litigation. The author discusses both Acts in detail, in the context of the current Covid-19 crisis. The author discusses both Acts in detail, in the context of the current Covid-19 crisis.